Effects of chemical defaunation on rumen fermentation pattern in cattle and buffaloes - Sahu, D S; Prasad, Krishna; Agrawal, I S; Verma, M L (The Indian Journal of Animal Sciences, 2012)
An experiment was designed to study the duration of effectiveness of sodium lauryl sulphate in defaunating the rumen contents and on the concentration of rumen metabolites. The rumen liquor samples were collected on 1, 10 and 20 days of administration of the chemical at, 0, 2, 4, 6 and 8 hr postfecding from fallnated and defaunated, fistulated bullocks in a 4-factor RBD. The rumen pH and total volatile fatty acids concentration in strained rumen liquor (SRL) did not differ significantly (P<0.05) on 1, 10 and 20 days of defaunation. However, the concentration of NH₃-N, TCA-soluble Nand total soluble N in SRL were significantly (P<0.05) lower on 20 day in comparison to 1 and 10 day. The rumen pH and NH₃-N concentration in SRL were higher in buffaloes and TVF A, TCA- Sol. N concentration were higher in cattle, The rumen pH, TVFA and NH₃-N concentration were significantly higher in defaunated category, whereas, TCA-Sol.N and total Sol.N concentration were significantly (P<0.05) lower in faunted animals.